Action, Detection and Shane Black Antiessentialist Genre Theory and Its Application - Bothmann, Nils (Springer Fachmedien Wiesbaden : VS, 2018)
Nils Bothmann applies antiessentialist genre theory to study the fusion of the action and the detection genre in the hybrid genre of detAction, focusing on the work of screenwriter and director Shane Black. After providing antiessentialist definitions of all three genres, the author undertakes close readings of Black's work in order to analyze depictions of race and gender as well as the role of intermediality and genre hybridity in detAction. Contents ■ Genre Theory ■ The Action Genre ■ The Detection Genre ■ The DetAction Genre ■ Close Readings of Shane Black's Work Target Groups ■ Lecturers and students of communication studies, English studies, film and media scientists and culture scientists ■ Practitioners in film and media industries The Author Dr. Nils Bothmann is a film and media scholar. His research interests include genre theory, action movies, gender and crime fiction.